Psychological Burnout for Teachers of Kindergarten Public and Private (A Contrastive Study) (Journal of the College of Education for Women, 2019)
The psychological burnout is considered one of dangerous phenomenon’s which appeared in the 70s of the 20th century and suffered by most of the society classes. It is a term which the wide uses and various meaning like emotional, mental, and physical exhaustion and chronic weak exhaustion. The presented research aims t identify the psychological burnout as for the Kindergarten teacher and the differences significance according to the variations (Kindergarten type: private or govern mental). The research sample contains 400 female teachers divided to 170 governmental Kindergarten teachers and 230 private Kindergarten teachers. The researcher prepared a measurement method to measure the psychological burnout for those teachers after a reference to the previous literature of studies in the field. The measurement includes 44 points in its final version. The researcher also measured the standard features of this measurement as for reliability and consistency in two methods: structural reliability and appearances reliability. Consistency in measured in two methods also: half division, alpha Cronback coefficient consistency. The research concludes: 1- Teachers of private and governmental Kindergarten do not suffer a psychological burnout. 2- Teachers of private Kindergarten suffers a psychological burnout more than the governmental ones.